Product Design - Alexandru, Cătălin; Jaliu, Codruta; Comşit, Mihai (IntechOpen, 2020)
Product design is a comprehensive process related to the creation of new products, and the ability to design and develop efficient products are key to success in today's dynamic global market. Written by experts in the field, this book provides a comprehensive overview of the product design process and its applications in various fields, particularly engineering. Over seven chapters, the authors explore such topics as development of new product design methodologies, implementation of effective methods for integrated products, development of more visualized environments for task-based conceptual design methods, and development of engineering design tools based on 3D photogrammetry, among others.